Homology modeling analysis of GSTD3 from Drosophila melanogaster / Kauthar Mohd Daud - Kauthar, Mohd Daud (2012)
Glutathione S-transferase is a detoxifying enzyme that responsible in catalyzing the conjugation of electrophilic xenobiotics compound with the thiol group of glutathione by biotransforming it into hydrophilic compound that can be eliminated from the cells via ion channel transport system. In Drosophila melanogaster, its GSTs have been divided into many classes in which two of them are organism specific, delta and epsilon. Members of delta GSTs which consist of 10 members are located at 3R chromosome. However, in delta isoform 3, there is truncation of several amino acids including conserved tyrosine residue at positions 5 and 6. Since D3 has been confirmed and observed to be expressed in pre adult development, therefore, I hypothesized that there is other tyrosine residue from different positions that have replaced the missing tyrosine. In order to determine the catalytic residue, homology modeling of D3 was carried out by taking 3EIN as template sequence. The template was obtained from UniProt database provided that stores protein sequences and functional information of the protein. Since I was interested in selecting the template with the experimental determined structure, therefore, 3EIN was selected as the suitable template. This is because, the sequence identity between target and template sequence was 63% whereby the model generated from this value could regarded as a good model. In building the model structure for query sequence, Modeller program command prompt was employed and the model was evaluated by PROCHECK program implemented by PDBSum database. After model evaluation, Swiss-PDBViewer and RasMol were used to visualized, manipulate and calculate the force field energy of the model. 3D structure of D3 showed that it consists of 2 beta sheets which were different from template, which consist of 4 beta sheets. Since GSTs usually work in homodimeric form, therefore, I suggested that D3 paired up with D3 by sharing their beta sheets. In term of catalytic residue, it suspected that other tyrosine residues from different position had compensated the missing tyrosine of positions 5 and 6. From the model visualization, it shows that side chain from tyrosine of positions 89 and 97 were projecting into the GSH binding site. Referring to the force field energy calculated, it shows that tyrosine of position 97 is more suitable since it has the lowest energy.